Dorsal wrist ganglia. Etiology. Clinic. Treatment - E. V. Ogorodnik; I. O. Golubev; M. R. Kalashnikova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The ganglia of the wrist joint, located on the back of the wrist, are one of the most common hand formations. They are tumor-like structures connected to the joint through a curved pedicle and filled with a gel-like fluid containing mucopolysaccharides. These formations are formed in the area of the navicular ligament. The causes of their occurrence are not fully understood, but factors such as constant physical exertion and hyperelasticity of ligaments may contribute to their development. The incidence is higher among women and the dorsal ganglion is usually not painful, being considered as a cosmetic problem. There is also the concept of a «hidden ganglion», which is not clinically apparent and can only be detected by specialized examination techniques such as magnetic resonance imaging or ultrasound.The objective was to analyze the possible causes of recurrence of the dorsal wrist ganglion after excision.